Albumin, hemoglobin, hypertrophy of left ventricular heart and quality of life in patients on renal replacement therapy - S. E. Urazlina; T. V. Zhdanova; A. V. Nazarov; T. V. Zueva (Лечащий Врач, 2021)
Left ventricular hypertrophy, hypoalbuminemia, and anemia are the risk factors for cardiovascular complications in patients with CKD 5. In addition, mortality from cardiovascular complications depends on the quality of life. In this regard, the purpose of this study was to study the structural parameters of the heart, hemoglobin and albumin levels in patients with CKD 5 on renal replacement therapy, depending on the quality of life indicators according to the SF-36 questionnaire. 65 patients on hemodialysis, peritoneal dialysis, and kidney transplant recipients were examined. Patients did not have clinical and laboratory signs of protein-energy insufficiency, blood hemoglobin was at least 100 g/l. All patients underwent general and biochemical blood tests, echocardiography, and SF-36 questionnaire. It has been shown that patients with CKD 5 on renal replacement therapy, with quality of life indicators below 50 points on the SF-36 scale, are more likely to have left ventricular myocardial hypertrophy, lower blood albumin and hemoglobin values.